Chemical modified coconut shell filled unsaturated polyester composites: a study on mechanical, thermal properties and morphology - Marliza Mostapha @ Zakaria (School of Materials Engineering, 2012)
The research is focused on the utilization of coconut shell (CS) as filler in unsaturated polyster (USP) composites. The USP/CS composites were produced using casting technique at room temperature. The effect of CS content on mechanical properties, thermal properties and morphology of USP/ CS composites were investigated.